Role of Agnikarma and Viddha Karma in Avabahuk W.S.R to Frozen Shoulder – A Conceptual Study - Bhardwaj, Upendra; Sharma, Vishnu Dutt (International Research Journal of Ayurveda & Yoga, 2023)
According to Sushruta’s definition of Avabahuk, this condition occurs when vitiated vata dosha enters the veins of the shoulder joint, causing the joint to be immobile and the arm muscles to atrophy. In the contemporary text, Avabahuk is comparable to Frozen Shoulder. Joints play a role in all bodily movements, but when they are damaged, it not only results in physical limitations but also has psychological effects including anxiety, impatience, and melancholy. The shoulder joint has the widest range of motion, and when it is injured, it restricts everyday tasks and worsens psychological conditions due to excruciating pain. The recovery from a frozen shoulder often takes 1–3 years, although this time frame is very challenging to achieve. Consequently, its treatment is important. Various measures are described in Ayurveda for its treatment. A parasurgical method called Viddha Karma uses pricking to remove the accumulated Doshas from the human body. Agnikarma, also known as a therapeutic heat burn, instantly relieves pain by balancing the local Vata and Kapha Dosha without causing any negative side effects. In addition, this treatment improves the patient’s quality of life by reducing the need for analgesics and other drugs.